The Protective Effects of Perceived Control During Repeated Exposure to Aversive Stimuli - Wang, Kainan S.; Delgado, Mauricio R. (Frontiers in Neuroscience, 2021)
The ability to perceive and exercise control is a major contributor to our mental and physical wellbeing. When faced with uncontrollable aversive stimuli, organisms develop heightened anxiety and become unwilling to exert effort to avoid the stimuli. In contrast, when faced with controllable aversive stimuli, organisms demonstrate behavioral vigor via avoidance attempts towards trying to seek and exercise control over the environment. As such, controllability confers protective effects against reduced avoidance motivation trigged by aversive environments. These observations beg the question of whether controllability can be potent enough to reverse passivity following repeated exposure to uncontrollable aversive stimuli and how this protective effect is encoded neurally. Human participants performed a Control in Aversive Domain (CAD) task where they were first subjected to a series of repeated uncontrollable aversive stimuli (i.e., aversive tones) across several contexts that were followed by a series of controllable aversive stimuli in a novel context. Faced with persistent uncontrollability, participants significantly reduced their avoidance attempts over time and biased towards giving up. However, the subsequent presence of controllability rescued participants’ avoidance behavior. Strikingly, participants who responded more strongly to the protective effects of control also had greater ventromedial prefrontal cortical (vmPFC) activation—a region previously observed to be associated with encoding the subjective value of control. Taken together, these findings highlighted the protective effect conferred by perceived control against passivity and offered insights into the potential role of the vmPFC in controllable environments, with implications for understanding the beneficial influence of perceived control on adaptive behavior.